2017
DOI: 10.1177/2324709617735135
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia: A Rare Cause of Pathological Fracture of the Femur

Abstract: The incidence rate of chronic lymphocytic leukemia (CLL) in the United States is approximately 0.005%; men are at slightly higher risk than women. Bony involvement or pathological fracture rarely occurs in CLL, and it may be the initial presentation. An 85-year-old woman presented with acute respiratory failure secondary to pneumonia. Symptomatology included dyspnea. She was found to have pathological fracture of the femur caused by CLL. The diagnosis of CLL had been made 6 years previously, but the patient ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…In 11 on 22 cases of the literature, patients had the axial skeleton or proximal long bones involved, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 and in rare cases, fractures were localized to the skull or facial bones. 17 , 22 , 23 Multiple fractures were reported in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In 11 on 22 cases of the literature, patients had the axial skeleton or proximal long bones involved, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 and in rare cases, fractures were localized to the skull or facial bones. 17 , 22 , 23 Multiple fractures were reported in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Some cases in literature have already described the presence of lytic lesions in patients affected by CLL, and one of them was previously described by our group. 10 In 11 on 22 cases of the literature, patients had the axial skeleton or proximal long bones involved [10][11][12][13][14][15][16][17][18][19][20][21] and in rare cases fractures were localized to the skull or facial bones. 17,22,23 Multiple fractures were reported in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
“…CLL is one of the most common hematologic malignancies in older adults, which clinical manifestations range from asymptomatic, thrombocytopenia, and lymph node, spleen, and liver infections 3,19 . Growing evidences have suggested that exosomes released by CLL were perceived to have essential regulatory roles in many disease‐related events, including TME and angiogenesis 10,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia (CLL) is a malignant tumor originating form hematopoietic tissue with complex etiology, and remains lack of effective treatment in current conditions 1 . According to clinical statistics, the susceptibility was higher in men than women, and genetic factors may occupy a certain position in the pathogenesis of the disease 1–3 . Additionally, CLL can transform into other malignant lymphoproliferative diseases, such as prolymphocytic leukemia, diffuse large B‐cell lymphoma, or Hodgkin lymphoma, which due to the continuous recirculation of leukemic cells to bone marrow and lymph nodes 4 .…”
Section: Introductionmentioning
confidence: 99%